Characterization of the mouse histone gene cluster on chromosome 13: 45 histone genes in three patches spread over 1Mb. - Wang, Z F; Krasikov, T; Frey, M R; Wang, J; Matera, A G; Marzluff, W F (Genome Research, 1996)
The histone gene cluster on mouse chromosome 13 has been isolated and characterized. Using overlapping YAC clones containing histone genes from chromosome 13, a contig of approximately 2 Mb has been defined. It contains 45 histone genes, organized in three patches containing tightly clustered genes. An 80-kb patch (patch III) containing 12 histone genes is near one end of the contig, and a similar-sized patch (patch I) containing 15 histone genes is near the other end of the contig, located at least 500 kb from the central patch (patch II) of histone genes. The entire cluster contains six histone H1 genes, including the testis-specific histone H1t gene that maps to the middle of the cluster. All nine histone H3 genes in this cluster have been sequenced, and their level of expression determined. Each histone H3 gene is distinct, with five genes encoding the H3.2 protein subtype and four genes encoding the H3.1 protein. They are all expressed, with each histone H3 gene accounting for a small proportion of the total histone H3 mRNA.